Organic Particles: Heterogeneous Hubs for Microbial Interactions in Aquatic Ecosystems - Bižić-Ionescu, Mina; Ionescu, Danny; Grossart, Hans-Peter (Frontiers in Microbiology, 2018)
Organic particles (hereafter particles) determine aquatic carbon pump efficiency, largely depending on microbial dynamics and activities. Current understanding is that particles sources dictate initial microbial colonization which is followed by rapid succession events as organic matter quality and nutrient content change due to microbial degradation. We applied a transcriptomic approach to assess the role of stochastic events on initial microbial colonization of particles. Furthermore, we asked whether gene expression corroborates rapid changes in carbon-quality. Commonly used fractionated filtration averages thousands of particles of different sizes, sources and ages. To overcome this drawback, we used replicate samples consisting of 3-4 pooled particles of identical source and age and further evaluated the consequences of averaging multiple particles. Using flow-through rolling tanks we conducted long-term experiments at near-in-situ conditions minimizing the traditional bottle-effect. Active microbial communities were highly heterogeneous despite an identical particle source, suggesting random initial colonization. Contrasting previous reports, expression of carbon utilization genes didn’t change after one week of incubation. Consequently, we suggest that in nature, changes in particle-associated community related to carbon availability are likely slow (days to weeks) due to constant supply of labile organic matter. Initial, random particle colonization seems to be subsequently altered by multiple organismic interactions shaping microbial community interactions and functional dynamics. Comparative analysis of pooled samples suggests that mechanistic studies of microbial dynamics should be done on single particles. The observed microbial heterogeneity and inter-organismic interactions may have important implications for evolution and biogeochemistry in aquatic systems.